2016
DOI: 10.4103/0189-6725.194667
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the use of laparoscopic-guided cholecystocholangiography and liver biopsy in definitive diagnosis of neonatal cholestatic jaundice

Abstract: Background:Once it is established that a jaundiced infant has direct hyperbilirubinemia, the principal diagnostic concern is to differentiate hepatocellular from obstructive cholestasis. Traditional tests such as ultrasonography, percutaneous liver biopsy and technetium 99 m hepatobiliary iminodiacetic acid (HIDA) scan are often not sufficiently discriminating. Definitive exclusion of biliary atresia (BA) in the infant with cholestatic jaundice usually requires mini-laparotomy and intra-operative cholangiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Liver biopsy is an invasive examination. There are many complications [29][30][31]. It reported that 5.8%-13.5% infants appear transient bacteremia after liver biopsy.…”
Section: The Shortcomings Of Liver Biopsymentioning
confidence: 99%
“…Liver biopsy is an invasive examination. There are many complications [29][30][31]. It reported that 5.8%-13.5% infants appear transient bacteremia after liver biopsy.…”
Section: The Shortcomings Of Liver Biopsymentioning
confidence: 99%
“…The current gold standard for the diagnosis of BA is exploratory laparotomy or intraoperative laparoscopic cholangiography, but this is an invasive examination method for children. [ 3 ] Abdominal ultrasound and hepatobiliary scintigraphy may be helpful in differentiating BA from other forms of IC. However, the accuracy of abdominal ultrasound is limited due to the experience of the operator.…”
Section: Introductionmentioning
confidence: 99%
“…Differentiation between BA and other forms of intrahepatic cholestasis (IC) is difficult. The current gold standard for the diagnosis of BA is exploratory laparotomy or intraoperative laparoscopic cholangiography, but this is an invasive examination method for children [3] . Abdominal ultrasound and hepatobiliary scintigraphy may be helpful in differentiating BA from other forms of IC.…”
Section: Introductionmentioning
confidence: 99%
“…However, patients may occasionally lack the symbolic signature for the early diagnosis of BA; thus, many of them may miss the optimal timing of surgical treatment. Intraoperative cholangiography and liver biopsy remain the gold standard for diagnosing BA, but they are invasive examination methods for children [14][15][16]. Although some markers and examinations have been proved distinct and have the potential for diagnosis of BA, an individual, ideal method has not yet been acknowledged.…”
Section: Introductionmentioning
confidence: 99%